Playing God in the meadow : how I learned to admire my weeds - Molnar, Martha Leb (Bright Leaf, an imprint of University of Massachusetts Press, 2022)
"After decades of fantasizing and saving, of working multiple jobs and embracing frugality in the midst of Manhattan, Martha Leb Molnar and her husband had found their parcel of land. Determined to turn an overgrown and unproductive Vermont apple orchard into a thriving and beautiful landscape, they decided to restore this patch of land to a pristine meadow and build a safe haven for their family and nearby wildlife. Once they cleared the gnarled and dying trees away, Molnar was forced to wage war on the invasive species that had sprung up around the property. Propelled by the heated debates surrounding non-native species and her own complicated family history and migration, she was driven to research the Vermont landscape, turning to scientific literature, experts in botany and environmental science, and locals who have long tended the land in search of answers. At turns funny, thoughtful, and conversational, Playing God in the Meadow follows this big city transplant as she learns to make peace with rural life and an evolving landscape that she cannot entirely control"--